Associations of digital competency and digital norms with digital professionalism among nursing students - Hana Yoo; Namhee Kim (The Journal of Korean Academic Society of Nursing Education, 2026)
Purpose: As healthcare is rapidly digitizing, strengthening digital professionalism among future nurses has become essential. However, empirical evidence on the factors associated with digital professionalism among nursing students is limited. This study aimed to assess the level of digital professionalism among fourth-year nursing students in South Korea and identify the factors of digital competency and digital norms associated with digital professionalism.Methods: A correlational design using self-report questionnaires was employed. Participants were fourth-year nursing students from three universities located in two metropolitan cities and one province. Based on G*Power, 184 questionnaires were distributed, and 173 valid questionnaires were analyzed. Data were collected from October 2 to November 29, 2024, after Institutional Review Board approval. IBM SPSS version 29.0 was used for descriptive statistics, independent t-tests, one-way ANOVA, Mann–Whitney U tests, Pearson’s correlation coefficient, and multiple linear regression.Results: Participants comprised 29 males (16.8%) and 144 females (83.2%). Significant factors associated with digital professionalism were digital norms (β=.37, p